Guianofruits A and B from the Fruit Oil of Andiroba (Carapa guianensis, Meliaceae) and Their Effects on LPS‐Activated NO Production. Issue 22 (8th June 2018) - Sasayama, Atsumi; Akita, Keiko; Oya, Hiroto; Kikuchi, Takashi; In, Yasuko; Fujitake, Mihoyo; Yamada, Takeshi; Tanaka, Reiko
Abstract: Two novel chukrasone‐type limonoids, Guianofruits A and B (1 and 2 ) were isolated from the fruit oil of Carapa guianensis AUBLET (Meliaceae), a traditional medicine in Brazil and Latin American countries. Their structures were elucidated based on spectroscopic analyses using 1D and 2D NMR techniques, HRFABMS, and X‐ray crystallography. Compounds 1 and 2 were rare chukrasone‐type limonoids that had once been isolated from Chukrasia tabularis . Compounds 1 and 2 were evaluated for their effects on the production of NO in LPS‐activated mouse peritoneal macrophages. The results of the NO inhibitory assay suggested that compound 1  is valuable as a potential inhibitor of macrophage activation. Abstract : Novel chukrasone‐type limonoids, named Guianofruits A (1 ) and B (2 ), were isolated from the fruit oil of Carapa guianensis (Meliaceae). These structures were established by spectroscopic analyses and X‐ray crystallography. The absolute structure of 1 was elucidated as 1 S, 3 S, 5 S, 10 R, 13 R, 17 R, and 2' R (Flack parameter of –0.20 (17) (CCDC 1529043)) and the value of Hooft y of –0.12 (13).